Patient reported outcome measures in a cohort of patients at high risk of breast cancer treated by bilateral risk reducing mastectomy and breast reconstruction. Issue 1 (January 2022) - Gandhi, A.; Duxbury, P.; Murphy, J.; Foden, P.; Lalloo, F.; Clancy, T.; Wisely, J.; Kirwan, CC; Howell, A.; Evans, D.G.
Summary: Background: Many women with increased lifetime risk of developing breast cancer, due to pathogenic gene variants or family history, choose to undergo bilateral risk reducing mastectomies (BRRM). Patient reported outcome measures (PROMS) are an increasingly important part of informed consent but are little studied in women undergoing BRRM. Methods: We used a validated PROMS tool for breast reconstruction (BREAST-Q) in 297 women who had BRRM and breast reconstruction, 81% of whom had no malignancy (Benign Group, BG) and 19% in whom a perioperative breast cancer was diagnosed (Cancer Group, CG). 128 women also completed a Hospital Anxiety & Depression Score (HADS) questionnaire to test if preoperative HADS score could predict PROMS outcomes. Results: Women in the CG had lower PROMS scores for satisfaction with their breasts, nipple reconstruction and sexual wellbeing. Both groups reported equal satisfaction with BRRM outcome and psychosocial well-being. Physical well-being PROMS of the abdomen and chest were high in women in both groups as were scores for satisfaction with the care they received. The CG group reported suboptimal quality of patient information. A higher presurgical HADS anxiety score predicted less favourable postoperative psychosocial well-being despite similar levels of satisfaction with aesthetic outcome. Conclusion: We show a high degree of patient reported satisfaction by woman undergoing BRRM and reconstruction. There was a negative association with a cancer diagnosis on quality of life PROMS and higher preoperative anxiety levels negatively affected postoperative psychosocial well-being. These important findings should be part of the informed consent process during preoperative counselling.